Influence of the wood mechanical properties in the dovetail joint behavior - Sobra, Karel (2015)
The force distribution inside a dovetail joint is complex. Wood is simultaneously loaded in different directions in the several connected surfaces. The analytical solutions available for the analysis of the behavior of those carpentry joints rely on the mechanical properties of wood. In particular, the stiffness properties of wood under compression are crucial for the forces equilibrium. Simulations showed that the stiffness values considered in each of the springs normally assumed in the analytical models, have great influence in the bearing capacity and stiffness of the dovetail joints, with important consequence on the stress distribution over the overall structure. In a wide experimental campaign, the properties under compression of the most common wood species of existing timber structures have been determined. Then, a solved example of a dovetail joint is presented assuming different wood species and the corresponding strength and stiffness properties values obtained in the tests.